COVID-19 AND MIGRANT WORKER: A CASE STUDY OF THE EDUCATION AND HEALTH OF CHILDREN OF MIGRANT WORKERS IN EAST LOMBOK DURING THE COVID-19 PANDEMIC - Hamdi, Saipul; Syarifuddin, Syarifuddin; Indrasari, Oryaza Pneumatica; Sayuti, Rosiady; Ihwani, Nia (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2022)
The phenomenon of migrant workers from Indonesia leads to numerous internal issues in the family. Parents who play a significant role in the family are unable to perform their duties to their full potential, particularly when it comes to supporting the growth of children in their health and education. Children who have their migrant worker parents abandon them frequently face a variety of disadvantages, such as poor health and educational opportunities. Children's education will undoubtedly be impacted, particularly in light of the Covid-19 epidemic, which has an effect on educational institutions. Their health is also in danger. Due to this circumstance, this article focuses on the education and health of migrant worker children as well as how they develop academically. This study was carried out over the course of six months (January–June 2022) In Suralaga, East Lombok utilizing qualitative techniques and a phenomenological perspective. Ways for gathering data by observations-participation, in-depth interviews, and documentation. The study included a sample of 30 respondents, including migrant workers, those who looked after their children, teachers, healthcare professionals, and local government. According to the findings of this study, migrant workers' children in Suralaga District generally lead happy lives. Children of migrant workers have good physical and educational outcomes, but they struggle with mental health issues. Therefore, especially during the Covid-19 pandemic, parents' attendance is crucial for their children's education and health.